SAT0191 Disease Progression in SSC-Overlap Syndromes is Significantly Different from Limited and Diffuse Cutaneous SSC. (23rd January 2014) - Moinzadeh, P.; Hunzelmann, N.; Krieg, T.; Blank, N.; Gerhard, F.; Genth, E.; Graefenstein, K.; Koetter, I.; Kreuter, A.; Melchers, I.; Pfeiffer, C.; Müller-Ladner, U.; et al.
Abstract : Background: Overlap syndromes are a very heterogeneous and remarkable group of patients, who present at least two connective tissue diseases (CTDs) at the same time, usually with a specific autoantibody status. Currently it is still debated, whether SSc patients showing signs of overlaps to other connective tissue diseases should be regarded as a specific disease subset. Objectives: To determine whether patients, classified as overlap syndromes, show a disease course different from patients with limited (lcSSc) and diffuse cutaneous SSc (dcSSc). Methods: We here present the data of a prospective study, involving well-defined 3323 patients, registered (with yearly follow-up informations) in a database of the German network for systemic sclerosis (DNSS). The following statistical methods were used: Kaplan-Meier analysis, cox regression, logistic regression, McNemar test as well as א 2 test/Fisher's exact test. Results: Among 3323 registered patients, 10% (325/3240) were diagnosed as SSc-overlap syndrome. Of these, 82.5% (268/325) were female with a mean age of 49, 2 ± 1.2 years. Significantly more of them developed musculoskeletal involvement, compared to lcSSc and dcSSc patients (37.8 %, 47.8%; p<0.0001) and carried significantly more often other antibodies (71.1%; p<0.0001), which were separated into U1RNP- (22.7%), Ro- (16.8%), PmScl- (11.5%) antibodies, followed by 10.8% with rheumatoid factors, 7.5% with La-, 5.8% with dsDNA- and 2.8% with Jo-1- and 2.6% with Ku-antibodies. The Kaplan-Meier analysis of the onset of organ involvement revealed a clear inclined position of overlap patients between patients suffering from lcSSc and dcSSc, especially regarding lung fibrosis and heart involvement. Patients suffering from PAH, oesophagus involvement and kidney involvement, overlap and lcSSc patients showed nearly similar curve progression (log rank<0.0001). Furthermore musculoskeletal involvement was significantly more frequent and more progressive in patients with overlap disease, followed by patients with dcSSc and lcSSc (log rank<0.0001). Conclusions: These data support the current concept, that SSc-overlap syndromes should be regarded as a separate SSc subset, distinct from lcSSc and dcSSc, due to a different course of the disease, different proportional distribution of specific autoantibodies and skin/organ involvement. Disclosure of Interest: None Declared